Making sense of the constitution : a primer on the Supreme Court and its struggle to apply our fundamental law - Frank, Walter M., 1945- (Southern Illinois University Press, 2012)
In Making Sense of the Constitution: A Primer on the Supreme Court and Its Struggle to Apply Our Fundamental Law, Walter Frank tackles in a comprehensive but lively manner subjects rarely treated in one volume. Aiming at both the general reader and students of political science, law, or history, Frank begins with a brief discussion of the nature of constitutional law and why the Court divides so closely on many issues. He then proceeds to an analysis of the Constitution and subsequent amendments, placing them in their historical context. Next, Frank shifts to th.